Indonesian Muslim Consumers' Perspectives and Behavior on Intentions to Use Islamic Financial Products Post-Covid-19 - Muhammad Alfarizi; Rini Kurnia Sari (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
This study was motivated by the importance of exploring the factors that influence people's intentions to buy or use Islamic financial products during the Covid-19 pandemic in Indonesia. Research with quantitative technique was carried out in the form of an online survey and tested using the structural equation model (SEM) method with the SmartPLS version 3.0M application. Sampling in this study used convenience sampling technique and obtained 456 respondents. The results of this study showed that almost all variables, namely religiosity, subjective norms, Islamic financial literacy, awareness, perceived behavioral control and attitudes were proven to be strong predictors of intention to use Islamic financial products. This research provides recommendations to various parties, both financial institutions, Islamic organizations and even the government need to collaborate to strengthen the level of Islamic financial literacy in the community. In addition, this study also provides recommendations to build public trust in the Islamic economy, especially Islamic banking through collaborative development of an Islamic economic roadmap including strengthening the role of Islamic banking both in terms of infrastructure and human resources. Various parties must come together to build a strong Islamic financial ecosystem and economic recovery post-Covid-19 to develop a prosperous and prosperous Indonesian economy in accordance with Islamic ideals as Rahmatan lil 'Alamin.